Rancang Bangun Aplikasi Kesehatan Mental Berbasis Android untuk Penyandang Disabilitas - Della Fitria Lestari; Endah Sudarmilah (The Indonesian Journal of Computer Science, 2025)
Persons with disabilities often face significant challenges in accessing mental health services due to limited infrastructure and a lack of specialized professionals in Indonesia. This group is particularly vulnerable to mental health issues, with the primary barriers being the absence of inclusive services and difficulties in accessing information and professionals who understand their specific needs, especially in communication. This study focuses on designing and developing an Android-based mental health application tailored for persons with disabilities. The application aims to provide accessible mental health information and consultation services with psychologists, supported by Sign Language Interpreters (SLI) to enhance communication. Developed using the System Development Life Cycle (SDLC) with the waterfall method, the application seeks to address the accessibility gap in mental health services. By improving access to information and support, the application is expected to help persons with disabilities overcome barriers to obtaining essential mental health care and resources.